Mobile Banking Transactions for Small and Medium Enterprise (SME) - Antonius David Wahyudi; Sesilya Kempa (Relevance: Journal of Management and Business, 2023)
Banks and SME actors cannot ignore mobile banking considering that it can provide efficiency in the financial transaction process, so it is necessary to know several factors that can influence transacting using mobile banking from SME actors. This study analyzes the effect of perceived risk, perceived ease of use, and institution-based trust on mobile banking transaction intention in SME actors. This research is quantitative research that aims to explain the relationship between several variables with a quantitative descriptive approach. The sample used in this study was 100 SME actors who were taken using a non-probability sampling technique. The results showed that the intention of transactions using mobile banking by SME customers was carried out on the basis of risk perception factors, perceived ease of use, and trust in bank institutions. The bank must socialize how to use and benefit from mobile banking to attract SME transactions to use mobile banking.